2015
DOI: 10.1038/oncsis.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Targeting self-renewal pathways in cancer stem cells: clinical implications for cancer therapy

Abstract: Extensive cancer research in the past few decades has identified the existence of a rare subpopulation of stem cells in the grove of cancer cells. These cells are known as the cancer stem cells marked by the presence of surface biomarkers, multi-drug resistance pumps and deregulated self-renewal pathways (SRPs). They have a crucial role in provoking cancer cells leading to tumorigenesis and its progressive metastasis. Cancer stem cells (CSCs) are much alike to normal stem cells in their self-renewal mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 145 publications
(149 reference statements)
4
120
0
3
Order By: Relevance
“…Therefore, a significant association between TERT promoter mutation and the in vitro sphere-forming capacity of GBM cells, identified in the present study, suggests that mutations in the TERT promoter region are associated with the biology of GBM cells to enhance self-renewal capacity. Self-renewal capacity is a key feature of GBM cancer stem cells that exert recurrence following anti-cancer treatments (24,25). Therefore, TERT promoter mutations resulting in overexpression of TERT may be associated with treatment resistance of GBMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a significant association between TERT promoter mutation and the in vitro sphere-forming capacity of GBM cells, identified in the present study, suggests that mutations in the TERT promoter region are associated with the biology of GBM cells to enhance self-renewal capacity. Self-renewal capacity is a key feature of GBM cancer stem cells that exert recurrence following anti-cancer treatments (24,25). Therefore, TERT promoter mutations resulting in overexpression of TERT may be associated with treatment resistance of GBMs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the negative clinical impacts of TERT promoter mutation or longer telomere length in a number of types of cancer, including GBMs (15,20,21,25,26). TERT promoter mutations may generate novel binding motifs for E26 transformation-specific/T-cell factor transcription Table II.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Aberrant regulation of the Wnt signaling pathway is known to play a role in tumorigenesis and maintenance of cancer stem cells. 3,4,28 The Wnt pathway can be activated aberrantly not only by mutations of genes functioning in Wnt signaling such as APC and CTNNB1 but also by dysregulation of secreted antagonists. For example, diminished expression caused by promoter methylation of Wnt antagonists genes sFRP1 and WIF1 results in unregulated increase of ligand-dependent Wnt signaling activity.…”
Section: Discussionmentioning
confidence: 99%
“…Já Embora o mecanismo não seja ainda conhecido, a inibição do Bmi-1 pode levar à inibição da proliferação e bloqueio da EMT (BORAH et al, 2015).…”
Section: Discussão __________________________________________________unclassified
“…Esta via foi descrita inicialmente em Drosophila e foi associada com o desenvolvimento embrionário. Em muitas neoplasias, a atividade da via Hedgehog encontra-se aumentada, promovendo o crescimento celular e controlando aspetos das CSCs como a auto-renovação (BORAH et al, 2015). Neste sentido, um dos principais pontos de regulação da via é por meio do controle da proteína de membrana SMO (MERCHANT;MATSUI, 2010).…”
Section: Discussão __________________________________________________unclassified